2021
DOI: 10.2147/dddt.s298355
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Bioequivalence Evaluation of Two Montelukast Sodium Chewable Tablets in Healthy Chinese Volunteers Under Fasted and Fed Conditions

Abstract: Purpose The aim of this study was to assess and compare the pharmacokinetic (PK) properties and bioequivalence of montelukast sodium chewable tablets prepared by two different manufacturers in healthy Chinese volunteers to obtain adequate PK evidence for the registration approval of the test formulation. Patients and Methods A randomized-sequence, single-dose, open-label, 2-period crossover study was conducted in fasted and fed healthy Chinese volunteers (Chinese Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Montelukast sodium OSF and CT had numerically similar PK parameters. Generally, these parameters were consistent with previous studies of montelukast sodium CT (15)(16)(17). Additionally, we found that C max decreased and T max increased under the fed conditions compared with the fasting conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Montelukast sodium OSF and CT had numerically similar PK parameters. Generally, these parameters were consistent with previous studies of montelukast sodium CT (15)(16)(17). Additionally, we found that C max decreased and T max increased under the fed conditions compared with the fasting conditions.…”
Section: Discussionsupporting
confidence: 93%
“…No AEs were observed in the fed trial. These safety results were consistent with previous data on montelukast sodium CT ( 15 - 17 ). There were two treatment-related AEs; one was in grade 1 and did not require treatment, while the other was in grade 2 and recovered after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Montelukast sodium belongs to a type of leukotriene antagonist that is selective. [7][8][9] It can prevent leukotriene from attaching to receptors, thus regulating inflammation while compensating for budesonide's limitations. [10][11][12] Therefore, to further investigate the clinical therapeutic effect of budesonide combined with montelukast sodium in bronchial asthma, 86 children with bronchial asthma admitted to our hospital from January 2019 to December 2020 were selected for the following study and report.…”
Section: Introductionmentioning
confidence: 99%
“…MP-AzeFlu Nasal Spray consists of a fixed-dose combination of azelastine hydrochloride (AZE) and fluticasone propionate (FLU) that is used for the relief of symptoms of moderate to severe seasonal (SAR) and perennial allergic rhinitis (PAR). 1 , 2 Due to different primary mechanisms of action of the individual agents, MP-AzeFlu nasal spray provides greater efficacy than therapy with each agent (azelastine hydrochloride and fluticasone propionate) alone. The fixed drug combination has been approved in 65 countries worldwide and it has been marketed in the US since September 2012 and in Europe since March 2013 for use by adults and adolescents aged ≥12 years and in the US since February 2015 for children aged ≥6 years.…”
Section: Introductionmentioning
confidence: 99%